Briozoários da plataforma continental do Ceará - Silva, Marcos Vieira da (2020)
Bryozoans are colonial, modular and sessile aquatic animals, which present a great diversity in the marine environment. These organisms can be found at different depths in the oceans, occurring from the intertidal zone to deeper regions such as abyssal zones. Only six species of marine bryozoans are known in Ceará, Brazil, this number being much lower when compared to other states in the Northeast region and even lower when compared to other regions of Brazil, such as Southeast and South. The purpose of this work was to study the bryozoofauna collected in the continental shelf of Ceará, taking into account biotic and abiotic aspects found in the Ceará platform that may influence the presence and absence of these organisms. The samples were obtained through dredging carried out on the west coast of the state of Ceará off the municipalities of Itarema, Acaraú and Camocim. 51 morphotypes of bryozoans were found, coming from the continental shelf of the state. 38 species were identified; 12 morphotypes were identified down to the genus level and only one superfamily level. The families most represented in the samples were Adeonidae, Antroporidae, Celleporidae, Lepraliellidae, Membraniporidae, Phidoloporidae and Schizoporellidae. Most of the bryozoans were found at depths ranging from 5 to 39 meters. In this study, the specimens found in Ceará were described and taxonomically discussed, with emphasis on the Gymnolaemata class, order Cheilostomata.